Problems and prospects of spa tourism development in Ukraine (in comparison with Central European countries) - Parfinenko, Anatolij; Volkova, Irina; Shcherbina, Viktoria (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2018)
The article considers the identification of problems and prospects of health, spa and wellness tourism development in Ukraine through the comparative analysis with similar markets of Central Europe. The authors choose such countries as Poland, Slovakia, Hungary and Czech Republic, which are the leaders not only in European but also in the world spa tourism market. Available healing resources and natural conditions, which are similar to European ones, make spa tourism one of the promising kinds of Ukrainian tourism development. The articles defines modern problems and main perspective directions of spa tourism development in Ukraine